Dinamika teori keputusan dalam perekayasaan pelaporan keuangan: Studi kritis dari perspektif rasionalitas hingga realitas perilaku di Indonesia - nabilla, nabilla (Maliki Interdisciplinary Journal, 2026)
This article analyzes the fundamental role of Decision Theory in the accounting paradigm shift from stewardship to decision usefulness. The research explores the dialectic between the normative approach based on Rational Choice Theory, which underpins international standards (IFRS), and the descriptive reality of Behavioral Accounting, which highlights cognitive limitations (Bounded Rationality) and behavioral biases (Prospect Theory). In the Indonesian context, the discussion focuses on the concept of financial reporting engineering as social engineering, as well as a critical evaluation of information failures in the financial manipulation case of PT Garuda Indonesia Tbk and the PT Asuransi Jiwasraya scandal. This research integrates the thoughts of UIN Maulana Malik Ibrahim Malang academicians, including the concept of the amanah metaphor as an ethical foundation, the use of the Beneish Ratio Index for fraud detection, and the influence of religiosity on whistleblowing intentions. The study concludes that the effectiveness of modern financial reporting depends not only on logical standard design but also on mitigating psychological biases through spiritual reinforcement and the use of quantitative forensic detection tools.